CHEMICAL COMPOSITIONAL ANALYSIS OF THE TAMARIX HISPIDA AERIAL PART EXTRACT OBTAINED IN ETHANOL SOLUTIONS OF DIFFERENT CONCENTRATION - Ikhsanov, Yerbol (Journal of Applied Engineering Science, 2018)
In this article, extracts from aerial part of Tamarix hispida Wild harvested in 2016 in the Ile District of the Almaty Region during the flowering period are considered. A comparative analysis of chemical composition of extracts obtained with three extracting agents constituting ethyl alcohol solutions concentrated differently (96%, 70%, 50%) has been made; the extracts were studied by high-performance liquid chromatography with a mass-selective detector Aligent Technologies 6400 Series Triple Quadrupole LC/MS, and were identified by mass spectra and retention times using the NIST library and Wiley LC/MS. In all the three extracts, various phthalic esters are dominant compounds, those are: Phthalicacid, octyl 2-pentylester in 96% extract, 1,2-Benzenedicarboxylicacid, decyloctylester in 70% extract, and Phthalicacid, hexadecyl 2-methylbutylester in 50% extract; also, a high content of alkaloids of various groups was identified in all the extracts, for example, 4-t-Butyl-2-(4-methoxy-phenyl)-6-p-tolyl-pyridine in 96% extract, Morphinan-4,6-diol, N-formyl-6-acetate (ester) in 70% extract, and 7-Methylthieno [3,2-b] pyridine in 50% extract. All of the above parameters are quite high for alkaloids in wild plants growing in Central Asia, while it should be noted that the highest alkaloid content is found in 70% alcohol extracts from aerial part of Tamarix hispida. Nitrogen-containing compounds are present in all the three extracts with the largest variety of compounds, with both nitrogen-containing dyes and alkaloids present therein. Apart from the above, a number of noteworthy metabolites containing halogens, such as Methyl (((1E)-2-(4-chlorophenyl)-3-[4-(2-furoyl)-1-piperazinyl]-3-thioxo-1-propenyl) amino) acetate (4,4%), Alclometasone Dipropionate have been identified in the 50% Tamarix hispida aerial part extract . Analysis of the literature data allows for a conclusion that a high content of nitrogen-containing compounds is characteristic of the Chenopodioídeae; thus, for example, plants of the Sueda genus, Halostachys and Ephedra are sources of alkaloids of the piperidine and pyrrole, pyrolidinium and morphine groups; however, the content of organic sulfur and organochlorine compounds in the Tamarix genus was not previously reported, although these classes are quite common in the Embryophytes.
Keywords: Tamarix hispida; HPLC-MS; anti-inflammatory activity; comparative analysis; ethanol extracts; chemical composition